2019
DOI: 10.1101/617803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordinated circadian timing through the integration of local inputs in Arabidopsis thaliana

Abstract: 29Every plant cell has a genetic circuit, the circadian clock, that times key processes 30 to the day-night cycle. These clocks are aligned to the day-night cycle by multiple 31 environmental signals that vary across the plant. How does the plant integrate 32 clock rhythms, both within and between organs, to ensure coordinated timing? 33To address this question, we examined the clock at the sub-tissue level across 34Arabidopsis thaliana seedlings under multiple environmental conditions and 35 genetic backgroun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 72 publications
5
52
0
Order By: Relevance
“…In addition, the timing difference of such interactions in the two organs indicates that the targets of the same protein pairs and their regulatory functions may be totally different. The results help to understand the fluctuations in the expression of the clock genes found in vasculature, mesophyll, and roots, as well as the periodicity differences between shoots and roots (Endo et al, ; Fukuda, Nakamichi, Hisatsune, Murase, & Mizuno, ; Gould et al, ; Greenwood, Domijan, Gould, Hall, & Locke, ; Marti & Webb, ).Therefore, further construction of the protein–protein network in aerial shoot or subterranean root system separately using circadian expression data, especially the identification of novel components contributing to organ‐specific modification of clock, helps to understand the temporal organization of cellular processes in both types of organs.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the timing difference of such interactions in the two organs indicates that the targets of the same protein pairs and their regulatory functions may be totally different. The results help to understand the fluctuations in the expression of the clock genes found in vasculature, mesophyll, and roots, as well as the periodicity differences between shoots and roots (Endo et al, ; Fukuda, Nakamichi, Hisatsune, Murase, & Mizuno, ; Gould et al, ; Greenwood, Domijan, Gould, Hall, & Locke, ; Marti & Webb, ).Therefore, further construction of the protein–protein network in aerial shoot or subterranean root system separately using circadian expression data, especially the identification of novel components contributing to organ‐specific modification of clock, helps to understand the temporal organization of cellular processes in both types of organs.…”
Section: Discussionmentioning
confidence: 96%
“…The lack of precision might provide circadian flexibility for rapid adjustments and improved responses in roots. Previous studies have reported spatial waves of clock gene expression with and within organs 40,42,45 that might be due to differences in period length and variable local coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments at different developmental stages and various growing conditions (e.g. light and temperature) will be required to confirm whether the long distance movement of ELF4 contributes or not to the spatial waves of clock gene expression observed in roots 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The strength of circadian cell-to-cell coupling differs among cells and tissues [ 114 , 115 ]. For example, coupling is minimum among cotyledon cells [ 116 ], variable in leaves [ 117 , 118 , 119 ], high in roots [ 120 ] and between the vasculature and neighbor mesophyll cells [ 121 ], and very high within cells at the shoot apex [ 122 ]. Long-distance circadian synchronization on the other hand, seems to occur through shoot-to-root photosynthetic signaling [ 123 ], light piping down the root [ 124 ] and by the movement of ELF4 from shoots to regulate the period of the root clock in a temperature-dependent manner [ 113 ].…”
Section: Future Perspectivesmentioning
confidence: 99%